Implementasi Metode Weighted Product dalam Sistem Pendukung Keputusan Penentuan Kualitas Sarang Burung Walet - Agung Prinato; Agus Sidiq Purnomo (Syntax Corporation Indonesia, 2023)
Technological developments are currently progressing rapidly and have been utilized by various fields to make calculations easier, more efficient and accurate. One of them is technology that was created to determine the best quality of a product so that the quality of the product can be determined. Likewise, determining the quality of swiftlet nests requires accurate calculations. Therefore, the use of a decision support system with the weighted product (WP) method is designed to obtain the best results in determining the precise and accurate quality of swiftlet nests. By using a system that has been designed with a weighted product (WP) method, it is hoped that it will make it easier to determine the quality of the best swallow's nest.